Step-by-step explanation:
- 2x-2y=-6
3x+4y=8
multiply equation (1) by 3 and equation (2) by 2
- 6x-6y=18
6x+8y=16
Add
2y=34
y= 34÷2
y=17
substitute 17 for y in equation (2)
3x+4y=8
3x+4(17)=8
3x+68=8
3x=8-68
3x=-60
x=-60÷3
x=-20
x=-20,y=17
Answer: 1 / 12
Step-by-step explanation:
1 / 4 x 1 / 3 = 1 / 12
Answer: 3j-6k+4
Step-by-step explanation:
First you have to distribute the 3 to the j and the -2k since they are both in the parentheses. So it would look like (3*j) +(-2k*3)+4 and if you simplify that it is 3j-2k+4. After that there are no like terms so that is your answer.